The Nexus Between Islamic Bank Financing For Msmes and Regional Poverty Reduction: Evidence From Indonesia - Arifa Pratami; Purwanto (International Journal of Management and Business Economics, 2026)
This study examines the nexus between Islamic bank financing and regional poverty reduction in Indonesia, addressing the critical gap in evidence-based policy during the post-pandemic recovery. Utilizing a balanced panel dataset of 33 provinces from 2020 to 2024, the research employs a Fixed Effect Model (FEM) with Cluster-Robust Standard Errors to ensure empirical rigor. The results demonstrate that while total Islamic financing significantly reduces poverty rates—confirming its role in wealth redistribution Islamic MSME financing exhibits a significant positive correlation. Rather than indicating intermediation failure, this study clarifies that such results reflect a strategic pro-poor targeting phenomenon, where Islamic financial institutions proactively penetrate high-poverty regions to fulfill their social inclusion mandate. Furthermore, the findings reveal a fiscal-monetary divergence, where regional government expenditure shows persistent inefficiencies in contrast to the positive externalities of population agglomeration. This study contributes to the literature by providing a nuanced understanding of the dual-objective nature of Islamic banking and offers a novel framework for integrating Sharia-based financial inclusion with regional development strategies. The findings provide a mandate for policymakers to synchronize fiscal allocations with Islamic financial ecosystems to foster sustainable economic independence.